Synopsis: Effects of agricultural mechanization on economies of scope in crop production in Nigeria - Takeshima, Hiroyuki; Hatzenbuehler, Patrick L.; Edeh, Hyacinth O. (International Food Policy Research Institute, 2018)
Economies of scope (EOS) refer to the economic benefits of producing multiple types of outputs rather than specializing in producing a specific output. EOS closely relates to the potential for crop diversification. Using panel data from farm households and crop-specific production costs in Nigeria, we estimate how the adoption of animal traction or tractors affects EOS between rice, non-rice grains, legumes/seeds, and other crops, which are the crop groups that are most widely grown with animal traction or tractors in Nigeria.